Creative Industries in Greece An Empirical Analysis from the Region of Epirus - Hyz, Alina; Karamanis, Kostas (Springer International Publishing : Imprint: Palgrave Macmillan, 2016)
Analyzing the role of creative industries, this book explores regional development within the economic cycle. Using the Greek region of Epirus as an in-depth case study, the authors identify the main opportunities for the region's development as well as the necessary conditions and constraints to achieve future economic growth. The last decade has seen creative industries receive growing attention from researchers, leading to an increasing body of analysis, studies and statistics. Despite this, they remain to be poorly understood and thus underestimated by many societies and policy makers, including those in the Greek economy. Creative Industries in Greece provides a close study of this sector and disseminates its best practices to examine its strengths, weaknesses, threats and opportunities. Alina Hyz is Professor of Business Administration at the Department of Accounting and Finance, Piraeus University of Applied Sciences, Greece. With both professional and teaching experience, her previous posts include Assistant Professor at the University of Lodz (1988-1997), postdoctoral research fellowship from the Greek Ministry of Education at the University of Macedonia, Thessaloniki and Robert Schuman scholar at the European Parliament, Directorate General for Research, Luxembourg. Kostas Karamanis is Associate Professor of Economics at the Department of Accounting and Finance, Technological Educational Institute of Epirus, Greece. He previously worked at the Greek Ministry of Employment from 2002-2011. Kostas' main research interests include market deregulation, competition and labour market, and his work has been published in international and Greek refereed journals.